El deslinde entre el juicio civil y la estafa en un negocio contractual según la jurisprudencia colombiana (2017)
In no small measure, the distinction between crime and civil wrong is very unclear. This leads to the filing of complaints, sometimes with the sole intention, why not say, to force a negotiation or at least to press for it to occur, denunciations that are finally filed in the Office of the Attorney General because, Character of last ratio that has Criminal Law, that it is appropriate that the matter in question be ventile in the Civil Jurisdiction. This article makes a jurisprudential analysis of the Supreme Court of Justice on the delimitation between the crime and the civil unlawful, in an attempt to help the lawyer in choosing the most appropriate way